Proceedings of the Eleventh Conference on Applied Linguistics (CONAPLIN 2018) 2019
DOI: 10.2991/conaplin-18.2019.320
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Metadiscourse in Finding and Discussion Section of Theses at English Department Universitas Negeri Jakarta

Abstract: Interactive metadiscourse is one of the sub categorizes of metadiscourse markers which refers to a feature used to construct and organize the information effectively in order to make coherent and convincing written text. Based on Hyland (2004), interactive metadiscourse consists of five categories, they are; transitions, frame markers, endphoric markers, evidentials, and code-glosses. The purpose of this study are to find out the types of interactive metadiscourse features used by English postgraduate students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The most frequent resources were 'and', 'because', and 'so'. This result seems consistent with the previous research that found extensive transition markers in abstract writing (Mazidah, 2019;Hamid, 2019). As previously mentioned, frame markers are used to set the structure of an abstract.…”
Section: Figure 1 Percentage Of Metadiscourse Markerssupporting
confidence: 92%
See 1 more Smart Citation
“…The most frequent resources were 'and', 'because', and 'so'. This result seems consistent with the previous research that found extensive transition markers in abstract writing (Mazidah, 2019;Hamid, 2019). As previously mentioned, frame markers are used to set the structure of an abstract.…”
Section: Figure 1 Percentage Of Metadiscourse Markerssupporting
confidence: 92%
“…In Indonesia, corpus-based research on metadiscourse was done by some academics, such as Hamid (2019) and Nugroho (2019). The first study aimed to determine the types of interactive metadiscourse markers used by postgraduate students in their finding and discussion section.…”
Section: Literature Reviewmentioning
confidence: 99%